1999
DOI: 10.1001/archneur.56.10.1283
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Hereditary Motor and Sensory Neuropathy Characterized by a Mild Phenotype

Abstract: Our findings indicate that the HMSN in this family represents a novel clinical and genetic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We also included the patient with CMT who had a potent novel mutation in the ARHGEF10 gene, as aforementioned. The phenotype of the patient was classified as the axonal type by neurophysiological testing, but the MCV was moderately slowed (median nerve MCV 41.7 m/s), as well as in previous studies 20 21. Verhoeven et al demonstrated the possibility that ARHGEF10 protein is associated with the developmental myelination of peripheral nerves using a mouse model.…”
Section: Discussionmentioning
confidence: 67%
“…We also included the patient with CMT who had a potent novel mutation in the ARHGEF10 gene, as aforementioned. The phenotype of the patient was classified as the axonal type by neurophysiological testing, but the MCV was moderately slowed (median nerve MCV 41.7 m/s), as well as in previous studies 20 21. Verhoeven et al demonstrated the possibility that ARHGEF10 protein is associated with the developmental myelination of peripheral nerves using a mouse model.…”
Section: Discussionmentioning
confidence: 67%
“…3B. Other genes that have been mapped to chromosome 10q21.1 near the MAWBP gene include the myxoid chondrosarcoma translocation gene (Shen et al 1990) and the Charcot-Marie-Tooth disease type 1D (CMT1D) gene (De Jonghe et al 1999). …”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…The mutation T 95 →M is a very common mutation in Europe and is associated with late‐onset axonal neuropathy and prominent sensory involvement (De Jonghe et al, ). This mutation alters the P0 glycosylation motif, resulting in the loss of glycosylation of the protein, which will be undigested by endoglycosidase (Grandis et al, ).…”
Section: Loss and Gain Of Glycosylation In P0 Human Protein From Poinmentioning
confidence: 99%